2018
DOI: 10.1038/s41598-018-34913-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gamma-Glutamyltransferase Levels are Associated with Cardiovascular Risk Factors in China: A Nationwide Population-Based Study

Abstract: Serum gamma-glutamyltransferase (GGT), which is mainly derived from the liver, is a sensitive marker of liver cell damage and oxidative stress. More recently, it has been found that increased GGT plasma activity is also associated with cardiovascular disease (CVD). However, data on the relationship between GGT and cardiovascular risk factors (CRFs) are lacking in nationally representative samples of the Chinese population. Here, we aim to investigate both the association between GGT and CRFs and CRF clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In this study, we evaluate the association between the ALDH2 rs671 polymorphism and major CRFs including hypertension, diabetes, obesity, and dyslipidemia. We used the following specific definitions, as previously described [22]:…”
Section: Definition Of Cardiovascular Disease Risk Factors (Crfs)mentioning
confidence: 99%
“…In this study, we evaluate the association between the ALDH2 rs671 polymorphism and major CRFs including hypertension, diabetes, obesity, and dyslipidemia. We used the following specific definitions, as previously described [22]:…”
Section: Definition Of Cardiovascular Disease Risk Factors (Crfs)mentioning
confidence: 99%
“…Recent studies have suggested that an increased serum alkaline phosphatase is a predictor of cardiovascular disease and vascular calcification [ 48 , 49 ]. In the same way, some studies have associated high serum levels of gamma-glutamyltranspeptidase with a high prevalence of CAD and cardiovascular risk factors [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Many studies have shown that GGT is correlated with traditional risk factors for CVD, such as TC, LDL-C, glucose, insulin, BMI, etc. [27][28][29][30][31][32] Further studies showed that higher GGT may increase cardiovascular mortality, [33][34][35][36][37][38] and is an independent predictor for future cardiovascular mortality. 39,40 Even within the normal range, higher GGT is associated with CVD risk factors, [41][42][43][44] suggesting GGT as a superior marker for predicting CVD risk.…”
Section: Discussionmentioning
confidence: 99%